New perspectives and research on Malaysian history essays on Malaysian historiography - Cheah, Boon Kheng (MBRAS monograph, 2007)
This book deals with the current research interests, methods, thingking and trend in Malaysian historical writing.The individual essays focus not only on new historical sources and methodologies, but also on debates between different schools of Malaysian histrorians on conceptual issues and on ways to reconstruct the Malaysian past. For a long time the primary object of Malaysian historical studies has been the nation-state, but some of the historians in this volume now argue that local history, social history, economic history and the role of women, minorities anad marginalized groups like trishaw riders are equally important concerns within Malaysia's socially diverse and multi-ethnic society. The essays also discuss challenges Malaysian historians face from new movements like post-modernism in representing historical truth and objectivity.